Law of normal distribution of ZTRK-complexes in the structure of urban formations - Tovbich, Valery; Kulichenko, Natalia; Sisoilov, Mykola (Transfer of innovative technologies, 2021)
ZTRK is a stop-territorial resource concentrator of town-planning formation of any level of hierarchy, in particular, ZTRK-system, which consists of several ZTRK-complexes formed by the corresponding ZTRK-units. ZTRK-unit is the "lowest" integral structured unit, which is the basis for the construction of urban formation of any level of hierarchy.